A Comparison of Histamine Receptor Antagonists Versus Proton Pump Inhibitor Gastrointestinal Ulcer Prophylaxis in Kidney Transplant Recipients. (March 2017) - Rouse, Ginger E.; Hardinger, Karen; Tsapepas, Demetra; Tichy, Eric M.
Introduction: There are several different agents that can be used for gastrointestinal (GI) ulcer prophylaxis in posttransplant recipients, such as histamine-2 receptor antagonists (H2RA) or proton pump inhibitors (PPIs). Research Question: This study was conducted to compare the incidence of adverse kidney events in transplant recipients who received prophylaxis with H2RAs or PPIs. Design: This retrospective study included all kidney transplant recipients from 3 transplant centers who were transplanted in 2009 through 2011. The primary objective was to compare the incidence of adverse events posttransplant, defined as the incidence of pneumonia, Clostridium difficile, hip fractures, GI bleeding, cytomegalovirus, organ rejection, and bacteremia. Results: A total of 211 patients were included in the study; of which 35 were included in the PPI group and 176 were included in the H2RA group. There were no significant differences between groups in regard to incidence of GI bleeding events or other adverse events. Discussion: These findings suggest there is a low incidence of GI ulcers and upper GI bleeding events after kidney transplantation with the use of H2RAs or PPIs. Additionally, there are similar rates of adverse events when comparing H2RAs versus PPIs for GI ulcer prophylaxis.